Cost-effectiveness analysis of a multiplex lateral flow rapid diagnostic test for acute non-malarial febrile illness in rural Cambodia and BangladeshResearch in context - Rusheng Chew; Chris Painter; Wirichada Pan-ngum; Nicholas Philip John Day; Yoel Lubell (Elsevier, 2024)
Summary: Background: Multiplex lateral flow rapid diagnostic tests (LF-RDTs) may aid management of patients with acute non-malarial febrile illness (NMFI) in rural south and southeast Asia. We aimed to evaluate the cost-effectiveness in Cambodia and Bangladesh of a putative, as-yet-undeveloped LF-RDT capable of diagnosing enteric fever and dengue, as well as measuring C-reactive protein (CRP) to guide antibiotic prescription, in primary care patients with acute NMFI. Methods: A country-specific decision tree model-based cost-effectiveness analysis was conducted from a health system plus limited societal perspective considering the cost of antimicrobial resistance. Parameters were based on data from a large observational study on the regional epidemiology of acute febrile illness, published studies, and procurement price lists. Costs were expressed in US$ (value in 2022), and cost-effectiveness evaluated by comparing incremental cost-effectiveness ratios with conservative opportunity cost-based willingness-to-pay thresholds and the more widely used threshold of per capita gross domestic product (GDP). Findings: Compared to standard of care, LF-RDT-augmented clinical assessment was dominant in Cambodia, being more effective and cost-saving. The cost per disability-adjusted life year (DALY) averted in Bangladesh was US$482, slightly above the conservative opportunity cost-based willingness-to-pay threshold of US$388 and considerably lower than the GDP-based threshold of US$2687. The intervention remained dominant in Cambodia and well below the GDP-based threshold in Bangladesh when antimicrobial resistance costs were disregarded. Interpretation: These findings provide guidance for academic, industry, and policymaker stakeholders involved in acute NMFI diagnostics. While definitive conclusions cannot be made in the absence of established thresholds, our results suggest that similar results are highly likely in some target settings and possible in others. Funding: Wellcome Trust, UK Government, Royal Australasian College of Physicians, and Rotary Foundation.